Determinants of an Effective Communication System in a Project Team - Muszyńska, Karolina (Advanced Information Technologies for Management – AITM 2008, 2008)
Effective project communication is one of the most important elements which determine project success. It is however difficult to achieve because of the multitude and variety of communication channels, project stakeholders and events that generate various kinds of information that has to be managed. In order to create an effective communication system in a project team such aspects as communication channels and communication forms within each channel, message information contents and time for response or delivery freąuency as well as specification of applicable telecommunication and information technology tools should be defined and described. Such a communication system should also include the whole project life cycle and all project stakeholders. All these issues constitute the determinants of an effective communication system, whose description and analysis is the subject of the present paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 126-133